Glucocorticoids in Rheumatic Diseases: Friend or Foe? - Vinall, Maria (MD Conference Express, 2007)
This article presents the results of a systematic review of 15 studies in early (duration up to 2 years) rheumatoid arthritis (RA) patients (n=1,414 patients), which indicates that glucocorticoids, in addition to standard therapy, can substantially reduce the rate of erosion progression in RA [Kirwan J et al. 2007;1:CD006356].